Answer:
C) (-1, -4) and (4, 6)
Explanation:
![\textsf{Equation 1}:y=2x-2](https://img.qammunity.org/2023/formulas/mathematics/high-school/6wu505bk3mwzh4pvos8fauro2bphx544xh.png)
![\textsf{Equation 2}:y=x^2-x-6](https://img.qammunity.org/2023/formulas/mathematics/high-school/oneepqajbjx64sn7vc6ocq66yl8dpchrfu.png)
Substitute Equation 1 into Equation 2 and solve for x:
![\implies 2x-2=x^2-x-6](https://img.qammunity.org/2023/formulas/mathematics/high-school/fpfopu6f5r23o8hbx4lekps18ln5txllzf.png)
![\implies x^2-3x-4=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/ffunv5iy2gcbhxrlh17tahmqy9fmgv6mfe.png)
Find two numbers that multiply to -4 and sum to -3: -4 and 1
Rewrite the middle term as the sum of these two numbers:
![\implies x^2-4x+x-4=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/spr7j2th07pq0ykdoccy9dpiq3qax3qxnv.png)
Factorize the first two terms and the last two terms separately:
![\implies x(x-4)+1(x-4)=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/f6v1nfhfnmu86pe8l2z3a7cz0ne7431o9l.png)
Factor out the common term
:
![\implies (x+1)(x-4)=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/uwdtdcrl3pm8khottu9zuizq6vbh95ntzu.png)
![\implies (x+1)=0 \implies x=-1](https://img.qammunity.org/2023/formulas/mathematics/college/pz0afgvtv9ekxi208op2ymphykwklihfsc.png)
![\implies (x-4)=0 \implies x=4](https://img.qammunity.org/2023/formulas/mathematics/college/ffzb6b9ygxekdmka88kjz8lj6giyjhhz1d.png)
Substitute the found values of x into Equation 1 and solve for y:
![x=-1 \implies y=2(-1)-2=-4](https://img.qammunity.org/2023/formulas/mathematics/high-school/eb2w5sjogglbh1kmw0rzk6fp62rxodntey.png)
![x=4 \implies y=2(4)-2=6](https://img.qammunity.org/2023/formulas/mathematics/high-school/iombjinuzp6wmbko0x7wyz1hhast4tp1jb.png)
Therefore, the solution to the system of equations is:
(-1, -4) and (4, 6)